Gas turbine performance - Walsh, Philip P.; Fletcher, Paul (Blackwell Science Oxford, 1998)
Gas Turbine Performance is an applied reference for all those who design, manufacture and operate gas turbines. It is a comprehensive and practical guide to all the main aspects of performance, including topics not well covered elsewhere, such as transient performance, starting, windmilling and analysis of engine test data. Gas Turbine Performance will meet a real need not only for those in the gas turbine industry, but also for gas turbine operators and purchasers such as airframe manufacturers, airlines and airforces, power utilities, the oil and gas industry and equipment suppliers. It will also be of significiant value to undergraduates of mechanical and aeronautical engineering.
Keywords: Gas turbines - Performance